2018
DOI: 10.1029/2017jg004378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use and Land Cover Change in Context of Growth Enhancements in the United States Since 1700: Net Source or Sink?

Abstract: Many flux-based data and related models indicate that the United States is currently a strong carbon sink, but this flux imbalance does not account for carbon lost from previous disturbance. Here we take a modeling approach that involves a full carbon accounting to include the effect of previous human-induced land use changes and management during a period of abiotic changes to the environment since the 1700s. The goal is to show how land use and land cover change has affected carbon loss in the context of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…In addition, land‐use change can create disturbances not followed by a typical recovery, often replacing the original forest ecosystem with one that has faster C turnover and smaller C storage capacity (Luo & Weng, 2011). For example, since 1700, land‐use change has led to a net loss of 42 Pg C in terrestrial C in the USA (Felzer & Jiang, 2018). Given the significant C loss caused by reduced forest recovery, it is necessary to closely examine forest regrowth to predict the future terrestrial C sink.…”
Section: Disturbance and Forest Regrowthmentioning
confidence: 99%
“…In addition, land‐use change can create disturbances not followed by a typical recovery, often replacing the original forest ecosystem with one that has faster C turnover and smaller C storage capacity (Luo & Weng, 2011). For example, since 1700, land‐use change has led to a net loss of 42 Pg C in terrestrial C in the USA (Felzer & Jiang, 2018). Given the significant C loss caused by reduced forest recovery, it is necessary to closely examine forest regrowth to predict the future terrestrial C sink.…”
Section: Disturbance and Forest Regrowthmentioning
confidence: 99%
“…Many land surface models did incorporate empirical relationships on management effect on soil and vegetation carbon. A recent literature is Felzer and Jiang (2018), who assessed…”
Section: P4 L2mentioning
confidence: 99%
“…Globally, during the 21 st century, land use and land cover change (LULCC) has accounted for 14% of the total anthropogenic carbon emissions (Friedlingstein et al, 2020). LULCC have been responsible for the largest losses of carbon from the land in the conterminous U.S. since the 1700s, with growth enhancements from CO2 fertilization and nitrogen deposition only partially countering this loss since the 1950s (Felzer and Jiang, 2018). Reforestation and afforestation have been the primary drivers for this enhanced sink (Kondo et al, 2018), especially growing back with rising CO2 levels (Strassmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few models (e.g. (Felzer and Jiang, 2018;Shevliakova et al, 2009)) have included forest demography, to accurately track the effects of disturbance in regrowing forests. Krause et al (2020) showed that including land legacy effects increases future carbon storage as ecosystems regrow and adapt to higher levels of CO2 and N deposition.…”
Section: Introductionmentioning
confidence: 99%